Algorithmic desire : toward a new structuralist theory of social media - Flisfeder, Matthew, 1980- (Diaeresis., 2021)
"Algorithmic Desire shows that social media is a metaphor that reveals the dominant form of contemporary ideology: neoliberal capitalism. The author interprets the social media metaphor through dialectical, Marxist, and Lacanian frameworks"--